The features of teaching english in primary schools in accordance with the concept of «The new ukrainian school» (Actual Problems of Psychology in Educational Institutions, 2018)
The article marks the main tendencies of reforming modern education. The author emphasizes the reorientation school teaching of foreign languages into communicative-activity, person-oriented and cultural trends, outlines the principles of English language teaching in primary schools in the system «The New Ukrainian School».
Keywords: primary education; foreign language education; communicative competence; communicative-activity orientation; junior schoolboy